Unveiling the Perceptions of Counselor Candidates: Metaphorical Perspectives into Mental Health and Self-Care Skills - Sebahat Sevgi Uygur (Van Yüzüncü Yıl Üniversitesi Eğitim Fakültesi Dergisi)
The goal of this study was to discover counselor candidates' perspectives on the concepts of "mental health of counselors" and "self-care skills of counselors." In this study, metaphor analysis, a discourse analysis method, was employed. The study included 106 third and fourth-year psychological counselor candidates (86 females, 26 males). A brief questionnaire consisting of two sentences was provided and counselor applicants were instructed to complete the statements using metaphors. Content analysis revealed five sub-themes, including analogies about mental health. The sub-themes are as follows: health and balance, diversity and individuality, elegance and sensitivity, strength and resilience, and movement and change. Five sub-themes about self-care skills were discovered. The sub-themes are as follows: Care and attention, artistic understanding and diversity, elegance and sensitivity, cleanliness and order, and energy and renewal. The findings revealed that counselor candidates addressed a wide range of mental health and self-care concepts. The variety of metaphors demonstrated how counselor applicants perceived and appreciated these concepts on a multifaceted and personal basis.